Systemic inflammation in patients with inflammatory joint diseases does not influence statin dose needed to obtain LDL cholesterol goal in cardiovascular prevention. Issue 8 (3rd April 2014) - Rollefstad, S; Ikdahl, E; Hisdal, J; Kvien, T K; Pedersen, T R; Holme, I; Semb, A G
Abstract : Objectives: There is a lipid paradox in rheumatoid arthritis describing that despite low lipids related to systemic inflammation, there is an increased cardiovascular (CV) risk. Our aim was to evaluate if baseline lipid levels or baseline systemic inflammation were associated with the statin dose sufficient to achieve lipid targets in patients with inflammatory joint diseases. Methods: In this longitudinal, short-term follow-up observational report, we evaluated 197 patients who did and 36 patients who did not reach the recommended low density lipoprotein cholesterol (LDL-c) target. The patients were, after CV risk evaluation, classified to either primary or secondary CV prevention with lipid lowering treatment (LLT). LLT was initiated with statins and adjusted until at least two lipid targets were achieved. Intensive LLT was defined as rosuvastatin ≥20 mg, atorvastatin and simvastatin at the highest dose (80 mg), and conventional LLT were defined as all lower doses. Results: In an independent sample t test, systemic inflammation or lipid levels at baseline were not associated with the statin dose (intensive or conventional) needed to achieve recommended LDL-c target (C reactive protein/erythrocyte sedimentation rate: p=0.10 and p=0.11, and LDL-c/total cholesterol: p=0.17 and p=0.34, respectively). The baseline inflammatory status and lipid levels in patients who did and did not obtain LDL-c goal were comparable (C reactive protein/erythrocyte sedimentation rate: p=0.32 and p=0.64, and LDL-c/total cholesterol: p=0.20 and p=0.83, respectively). Conclusions: Systemic inflammation or lipid levels did not influence the intensity of statin treatment needed to obtain guideline recommended lipid targets in CV prevention. Whether the background inflammation in patients with inflammatory joint diseases over time influences the CV risk reduction related to statins is yet unknown.